An electrochemical electrode, its preparation method and use
Patent Information
- Application Number
- CN202610995925.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-27
AI Technical Summary
本发明提供的电化学电极能够很好地对水中的氨和镉离子含量等进行检测,具有响应快、抗干扰性强、精度高等优点,可解决现有氨和镉离子检测方法操作繁琐、成本较高、难以现场快速检测等技术难题,为水中氨和镉离子的实时监测和预警提供更有效的技术手段
[0047]根据本发明实施例,Ti3C2Tx的高导电性为B-GQDs与氨分子或镉离子之间反应产生的电子提供了高速传输通道,显著促进了异相电子转移,放大了检测信号。
Smart Images

Figure CN122983156A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of detection technology, and in particular to an electrochemical electrode, its preparation method, and its application. Background Technology
[0002] Ammonia and cadmium ions are two key indicators affecting water quality safety, and they often coexist in water bodies polluted by aquaculture wastewater and industrial emissions. Excessive ammonia concentrations in water not only easily induce eutrophication but also directly poison aquatic animals, affecting their growth, development, and even survival. Cadmium ions, as a highly toxic heavy metal, are persistent and bioaccumulate, and can enter the human body through the food chain, causing serious health risks such as kidney damage and bone diseases. In the fields of aquaculture and water environment monitoring, achieving simultaneous and rapid detection of ammonia and cadmium ions is of significant practical importance for ensuring the safety of aquatic products and the ecosystem.
[0003] Currently, the mainstream techniques for ammonia determination in water include spectrophotometry, fluorescence analysis, and electrochemical analysis. Spectrophotometry primarily achieves quantitative analysis by detecting the color change produced when ammonia reacts with chromogenic reagents (such as salicylic acid, Nessler's reagent, and indophenol blue). It is a commonly used laboratory method and typically offers high accuracy, but it involves complex sample pretreatment steps, making it difficult to meet the needs of rapid on-site detection. Fluorescence analysis is simple to operate; however, its detection accuracy depends on large fluorescence spectrometers, making real-time in-situ detection difficult. For cadmium ion detection, the mainstream methods are atomic absorption spectrometry and inductively coupled plasma mass spectrometry (ICP-MS), which offer high accuracy but require expensive equipment and complex pretreatment.
[0004] Electrochemical methods have attracted much attention due to their high sensitivity and the ability to miniaturize instruments; however, the long-term stability and anti-interference capabilities of traditional electrochemical electrodes still need improvement. Therefore, developing a novel, environmentally friendly, and stable electrode modification material to achieve highly sensitive and rapid joint detection of ammonia and cadmium ions in water is a pressing technical problem. The selection and modification of electrode modification materials are key approaches to improving the performance of electrochemical sensors.
[0005] Patent application CN202311746416.3 discloses a platinum-nickel alloy electrochemical sensor and its preparation method. This sensor uses nickel foam as a substrate, and a platinum-nickel alloy catalytic layer is in-situ electrodeposited on the surface of the nickel foam using a chronoamperometry method. Ammonia in water is then detected using cyclic voltammetry or differential pulse voltammetry. However, while platinum, as a precious metal, has excellent catalytic performance, its cost is high, and the stability and anti-poisoning ability of its alloy electrode during long-term use still need further verification. Patent application CN202480058948.4 discloses an electrochemical detection device. A formulation containing phenol derivatives and nitroprusside coupling agent precursors is quantitatively loaded onto the surface of a screen-printed carbon working electrode. An active coupling agent is generated through in-situ electrochemistry, followed by a Berthelot reaction to generate indophenol products. Finally, differential pulse voltammetry is used to quantitatively detect ammonia. This method combines colorimetric chemistry with electrochemical detection, exhibiting high selectivity and sensitivity. However, the working electrode coating of this sensor involves multi-component chemical agents, making the preparation process relatively complex. Furthermore, the sample pretreatment step increases operational complexity, hindering rapid on-site detection. Patent application CN202311060372.9 discloses an electrochemical sensor that uses an electrode with Fe / N-mCS metal composite material modified on the surface of a screen-printed carbon electrode as the working electrode, detecting the electrochemical signals of cadmium ions at different concentrations using square-wave anodic stripping voltammetry. This sensor is simple to prepare and has low detection costs. However, its anti-interference capability in real water samples requires further verification.
[0006] Quantum dot materials, such as carbon quantum dots and graphene quantum dots, have recently shown promise in the field of electrochemical sensing due to their advantages such as large specific surface area, tunable surface functional groups, and environmental friendliness. However, single quantum dot materials often suffer from insufficient conductivity and limited dispersion of catalytic sites, making it difficult to fully realize their efficiency in electrochemical detection. Furthermore, quantum dots lack specificity for ammonia and cadmium ions, making detection susceptible to interference from other ions. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides an electrochemical electrode, its preparation method, and its application. The electrochemical electrode provided by this invention can effectively detect the content of ammonia and cadmium ions in water, exhibiting advantages such as rapid response, strong anti-interference capability, and high accuracy. It solves the technical difficulties of existing ammonia and cadmium ion detection methods, such as cumbersome operation, high cost, and difficulty in rapid on-site detection, providing a more effective technical means for real-time monitoring and early warning of ammonia and cadmium ions in water.
[0008] In a first aspect, the present invention provides an electrochemical electrode comprising a substrate and a sensitive modification material attached to the substrate; the sensitive modification material is B-GQDs (boron-doped graphene quantum dots) and Ti3C2T. xComposite materials of (monolayer or few-layer titanium carbide) (B-GQDs / Ti3C2T) X The substrate is a screen-printed electrode. This invention constructs a B-GQDs / Ti3C2T-based electrode... x Electrochemical electrodes modified with composite sensitive materials exhibit selective recognition of ammonia molecules through the electron-deficient boron sites of B-GQDs and the reducing ability of B-GQDs for cadmium ions. (Ti3C2T) x As a highly conductive two-dimensional carrier, it can effectively disperse B-GQDs and provide a fast electron transport channel. The synergistic effect of the two enables this modified electrode to exhibit excellent performance such as fast response, high sensitivity, and good selectivity for ammonia and cadmium ions in water. Within a certain concentration range, the peak current shows a good linear relationship with the concentration, providing a simple and sensitive technical means for the rapid on-site detection of ammonia and cadmium ions in the aquatic environment.
[0009] According to the present invention, the surface of B-GQDs is rich in oxygen-containing functional groups such as -OH and -COOH, while Ti3C2T x It has abundant surface functional groups (T x Terminal groups (such as -O, -OH, and -F) can be used to achieve stable complexation between the two through hydrogen bonding and electrostatic interactions. Ti3C2T x As a two-dimensional carrier, Ti3C2T effectively disperses B-GQDs due to its ultra-high specific surface area, suppressing quantum dot aggregation caused by π-π stacking and significantly increasing the number of exposed recognition sites. Meanwhile, Ti3C2T... x The metallic conductivity can be used to construct a highly efficient heterogeneous electron transfer network, which can quickly conduct the electrical signals generated by B-GQDs recognizing ammonia molecules or cadmium ions to the electrode surface, and significantly improve the electrochemical response sensitivity to ammonia and cadmium ions under synergistic effect.
[0010] Preferably, the B-GQDs and Ti3C2T x The mass ratio is 1~10:1~30. A suitable mass ratio is beneficial for B-GQDs in Ti3C2T. X The layered surface dispersion and improved electrode conductivity contribute to the excellent current signal at the aforementioned mass ratio. However, when B-GQDs are combined with Ti3C2T... x If the mass ratio exceeds the above range, a thicker film will be formed, which will hinder electron transfer and ion diffusion at the electrode-electrolyte interface, resulting in a decrease in current signal.
[0011] Preferably, the preparation of the electrochemical electrode includes: preparing a mixture of the B-GQDs and Ti3C2T. x A mixed composite material dispersion; the composite material dispersion is drop-coated onto the working electrode area of a screen-printed electrode and then dried.
[0012] Further preferably, the preparation of the B-GQDs includes: using boron-containing precursors and carbon sources as raw materials, and preparing them through a hydrothermal reaction.
[0013] Further preferred, the Ti3C2T x The preparation process includes mixing Ti3AlC2 with a fluorine-containing etching solution, followed by selective etching and ultrasonic stripping.
[0014] Secondly, the present invention provides a method for preparing the electrochemical electrode, comprising: 1) A boron-containing precursor and a carbon source are mixed and subjected to a hydrothermal reaction to obtain B-GQDs.
[0015] 2) Ti3AlC2 was mixed with a fluorine-containing etching solution, and then selectively etched and ultrasonically stripped to obtain Ti3C2T. x .
[0016] 3) The B-GQDs and Ti3C2T x The mixture is combined with a solvent, and then subjected to ultrasonication and stirring to obtain a dispersion.
[0017] 4) The dispersion is drop-coated onto the working electrode area of the screen-printed electrode and dried. The electrochemical electrode prepared by this invention uses a commercially available screen-printed electrode as a substrate, B-GQDs / Ti3C2T X This invention provides a sensitive material for modifying the working electrode. The preparation process is simple, using boron-containing precursors and carbon sources as raw materials, followed by a hydrothermal reaction to obtain B-GQDs. Using Ti3AlC2 as a raw material, monolayer or few-layer Ti3C2T is obtained through selective etching and ultrasonic exfoliation. x Nanosheets. The B-GQDs are combined with the Ti3C2T... x Nanosheets were mixed in a specific ratio (using deionized water, methanol, or a mixture of both as solvent), and then composited by ultrasonication and stirring to obtain B-GQDs / Ti3C2T. x Composite material dispersion. The B-GQDs / Ti3C2T... x The composite material dispersion was drop-coated onto the working electrode area of a commercially available screen-printed electrode, and after drying, B-GQDs / Ti3C2T was obtained. x Composite-modified electrochemical electrode. The method of this invention utilizes a composite material B-GQDs / Ti3C2T... x As sensitive modification materials for the working electrode, the two complement each other in structure and function, jointly achieving sensitive electrochemical detection of ammonia and cadmium ions in water.
[0018] Preferably, in step 3), the B-GQDs and Ti3C2T xThe mass ratio is 1~10:1~30, for example 1:1, 1:2, 2:3, 2:5, 4:3, 4:5, 4:7, 5:7, 5:12, 5:16, 5:24, 6:7, 6:20, 6:30, etc., preferably 1~5:3~15, more preferably 3:4~10. In this invention, by using the above-mentioned ratio of B-GQDs and Ti3C2T X Especially at the aforementioned preferred dosage ratio, it helps B-GQDs in Ti3C2T X The dispersion of the layered structure surface and the improvement of electrode conductivity facilitate the subsequent acquisition of highly sensitive detection current.
[0019] Preferably, in step 3), the concentration of the dispersion is 0.02~0.5 mg / mL, more preferably 1.8~2.5 mg / mL.
[0020] Further preferred, in step 3), the B-GQDs and the Ti3C2T x Nanosheets were mixed in a solvent in a certain proportion to form a dispersion, and after ultrasonic treatment and stirring, B-GQDs / Ti3C2T were obtained. x Composite material dispersion.
[0021] Further preferably, the solvent is deionized water, ethanol, methanol, or a mixture thereof, preferably a 95% methanol solution.
[0022] Further optimization involves ultrasonic treatment for 30–90 min and magnetic stirring at room temperature for 6–24 h to ensure that B-GQDs are fully loaded onto Ti3C2T. x Nanosheet surface.
[0023] Preferably, in step 1), the boron-containing precursor and the carbon source are dissolved in a first solvent and subjected to a hydrothermal reaction to obtain a B-GQDs solution.
[0024] In this invention, B-GQDs are prepared via a one-step hydrothermal method using a boron-containing precursor and a carbon source. During the hydrothermal process, the carbon source molecules undergo dehydration, polymerization, and carbonization to form a graphene quantum dot framework, while boron atoms are simultaneously doped into sp. 2 In the carbon lattice, an electron-deficient p-type doped structure is formed. At the same time, the surface of B-GQDs is rich in hydrophilic functional groups such as -OH and -COOH, and has excellent electron-withdrawing properties, providing abundant electron-deficient active sites for the subsequent selective recognition of ammonia molecules and cadmium ions.
[0025] More preferably, the boron-containing precursor is selected from one or more of boric acid, phenylboronic acid, or sodium borohydride; and the carbon source is selected from one or more of graphene, citric acid, glucose, or ascorbic acid.
[0026] More preferably, the molar ratio of the boron-containing precursor to the carbon source is 0.1 to 1:1.
[0027] More preferably, the first solvent is deionized water or an ethanol / water mixture.
[0028] Further preferably, the hydrothermal reaction is carried out at a temperature of 160~200 ℃ for a time of 6~12 h.
[0029] Further preferably, the hydrothermal reaction includes a dialysis purification step: using a dialysis bag of 500~2000 D, using deionized water as the dialysis solution, dialysis time of 24~48 h, and changing the dialysis solution every 8~12 h to obtain a pure B-GQDs solution; optionally, it also includes drying at 35~45℃.
[0030] Preferably, in step 2), Ti3AlC2 is mixed with a fluorine-containing etching solution, and then selectively etched and ultrasonically peeled off to obtain a single layer or few layers of Ti3C2. x Nanosheets; the fluorine-containing etching solution is preferably an etching system generated in situ from hydrochloric acid and lithium fluoride.
[0031] In this invention, a mild etching strategy involving the in-situ generation of hydrofluoric acid from hydrochloric acid / lithium fluoride is used to selectively remove the aluminum atom layer in Ti3AlC2, resulting in a layered Ti3C2T structure. x This method is safe to operate and is beneficial for use in Ti3C2T. x The surface is rich in terminal functional groups such as -O, -OH, and -F. Subsequent ultrasonic exfoliation yields single-layer or few-layer nanosheets with ultra-high specific surface area and excellent metallic conductivity, which can effectively load B-GQDs and provide high-speed electron transport channels.
[0032] Further preferably, the monolayer or few-layer titanium carbide is prepared by selective etching: Ti3AlC2 powder is added to a fluorine-containing etching solution, stirred and reacted, centrifuged and washed until neutral, and then ultrasonically exfoliated to obtain a monolayer or few-layer Ti3C2T. x Nanosheet dispersion.
[0033] Further preferably, in the hydrochloric acid / lithium fluoride etching system, the concentration of hydrochloric acid is 6~12 mol / L, and the mass ratio of lithium fluoride to Ti3AlC2 is 0.8~1.5:1.
[0034] Further preferably, the etching reaction is carried out at a temperature of 35~60 ℃ for a time of 24~48 h.
[0035] Further preferably, the centrifugal washing uses deionized water, and the washing is repeated until the pH of the supernatant is 6-7.
[0036] Further preferably, the ultrasonic ablation is performed under an inert atmosphere (such as nitrogen or argon), the ultrasonic time is 1-4 h, and the ultrasonic power is 100-300 W.
[0037] Further optimization involves ultrasonic exfoliation followed by centrifugation at 3500–5000 rpm for 20–40 min, collecting the supernatant to obtain monolayer or few-layer Ti3C2T. x Nanosheet dispersion.
[0038] Preferably, in step 4), the B-GQDs / Ti3C2T obtained in step 3) is used. x The composite material dispersion was drop-coated onto the working electrode area of a commercially available screen-printed electrode and dried to obtain B-GQDs / Ti3C2T. x Composite modified electrochemical electrode.
[0039] In this invention, a simple drop-coating method is used to coat B-GQDs / Ti3C2T x The composite material can be directly modified onto the working electrode surface of a commercially available screen-printed electrode, offering convenient operation, good reproducibility, and suitability for mass production. By controlling the number of drop coatings and the volume, the thickness of the modified layer and the loading of active materials can be adjusted, thereby optimizing electrochemical detection performance.
[0040] Further preferably, the drop volume is 2~20 μL.
[0041] More preferably, the drying process involves air drying at room temperature, drying in an oven at 40-60°C for 30-60 minutes, or drying with an infrared lamp.
[0042] Further preferably, the drop-drying process is repeated 1 to 3 times to control the thickness and load of the modified layer.
[0043] Further preferably, the commercial screen-printed electrode is an integrated chip of three electrodes: a carbon working electrode, a silver / silver chloride reference electrode, and a carbon counter electrode.
[0044] Thirdly, this invention provides the application of the above-described electrochemical electrode or the electrochemical electrode prepared by the above-described method in water quality detection; preferably, its application in the detection of ammonia content and / or cadmium ion content in water. In this invention, at potentials of -0.5V and -0.9V, the peak current of the electrode oxidation peak shows a good linear relationship with ammonia (10~60 μmol / L) and cadmium ion (10~80 μmol / L), respectively, which can effectively detect the ammonia and cadmium ion content in water bodies in fields such as aquaculture and environmental monitoring.
[0045] According to embodiments of the present invention, B-GQDs possess a unique electronic structure due to boron atom doping: the outermost shell of a boron atom has only three electrons, which replace carbon atoms in the sp...2 After hybridization of the carbon framework, an electron-deficient p-type doped structure is formed, resulting in numerous electron-deficient active sites on the surface of B-GQDs, exhibiting overall electron-withdrawing properties. The nitrogen atom of the ammonia molecule in water carries a lone pair of electrons, making it a typical Lewis base. When an ammonia molecule approaches the surface of B-GQDs, its lone pair of electrons undergoes coordination electron transfer to the electron-deficient boron sites, altering the electron cloud density and carrier concentration of the B-GQDs. Furthermore, the interaction between cadmium ions and B-GQDs allows the B-GQDs to act as a reducing agent, donating electrons to cadmium ions to form cadmium. Under a certain applied voltage, this perturbation of the electronic structure significantly affects the charge transfer kinetics at the electrode interface, thereby achieving a sensitive electrochemical response to ammonia and cadmium ions.
[0046] According to embodiments of the present invention, B-GQDs and Ti3C2T x The abundant terminal functional groups such as -O, -OH, and -F on the surface can also promote the pre-enrichment of ammonia molecules or cadmium ions in water at the electrode interface through hydrogen bonding and other interactions, thereby increasing the effective reaction area. Monolayer or few-layer titanium carbide (Ti3C2T) x It possesses a two-dimensional layered structure, ultra-high specific surface area, and excellent metallic-grade conductivity. Therefore, Ti3C2T x The introduction of this technology can effectively load and disperse B-GQDs, preventing quantum dots from agglomerating due to π-π stacking. This significantly increases the number of exposed recognition sites, thereby accelerating the electron transfer rate of ammonia molecules or cadmium ions during the electrochemical dissolution process. This results in a significant enhancement of the dissolution peak current signal, enabling highly sensitive electrochemical detection of ammonia and cadmium ions.
[0047] According to an embodiment of the present invention, Ti3C2T x The high conductivity provides a high-speed transmission channel for electrons generated by the reaction between B-GQDs and ammonia molecules or cadmium ions, which significantly promotes heterogeneous electron transfer and amplifies the detection signal.
[0048] The beneficial effects of the present invention are at least as follows: the B-GQDs / Ti3C2T prepared by the present invention x The composite modified electrode combines the selective recognition ability of B-GQDs for ammonia or cadmium ions with that of Ti3C2T x Its high conductivity and high specific surface area enable it to produce a sensitive and rapid electrochemical response to ammonia or cadmium ions in water. Within a certain range of ammonia and cadmium ion concentrations, the peak current of differential pulse voltammetry (DPV) shows a good linear relationship with the concentration. It has high detection sensitivity, good selectivity, and fast response speed, providing a simple and effective technical means for the rapid on-site detection of ammonia and cadmium ions in the aquatic environment. Attached Figure Description
[0049] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0050] Figure 1 B-GQDs / Ti3C2T synthesized for embodiments of the present invention x Transmission electron micrograph of the composite material.
[0051] Figure 2 B-GQDs / Ti3C2T prepared for embodiments of the present invention x Scanning electron microscope image of the modified electrode.
[0052] Figure 3 B-GQDs / Ti3C2T in the embodiments of the present invention x Standard curve of modified electrode against ammonia.
[0053] Figure 4 B-GQDs / Ti3C2T in the embodiments of the present invention x Standard curve of modified electrode for cadmium ions.
[0054] Figure 5 B-GQDs / Ti3C2T in the embodiments of the present invention x Repeatability results of ammonia detection using modified electrodes.
[0055] Figure 6 B-GQDs / Ti3C2T in the embodiments of the present invention x Repeatability results of cadmium ion detection using modified electrodes.
[0056] Figure 7 B-GQDs / Ti3C2T in the embodiments of the present invention x Batch-to-batch repeatability testing of modified electrodes.
[0057] Figure 8 B-GQDs / Ti3C2T in the embodiments of the present invention x Results of the anti-interference performance of the modified electrode.
[0058] Figure 9 B-GQDs / Ti3C2T in the embodiments of the present invention x The optimal response time for the modified electrode to detect ammonia and cadmium ions.
[0059] Figure 10 These are the test results for modified electrodes with different mass ratios in the embodiments of the present invention. Detailed Implementation
[0060] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0061] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0062] Unless otherwise specified, the techniques or conditions described in the embodiments of this invention shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Devices, instruments, reagents, etc., without specified manufacturers, are all conventional products that can be purchased through legitimate channels. All experimental reagents and raw materials involved are commercially available products, and all reagents are analytical grade products.
[0063] Example 1 This embodiment provides a B-GQDs / Ti3C2T x The synthesis method of nanocomposite materials is as follows: 1) Preparation of B-GQDs: 1.0 g citric acid and 0.15 g boric acid were dissolved in 30 mL deionized water and stirred until completely dissolved. The solution was placed in a 100 mL hydrothermal reactor and reacted at 180 °C for 10 h. After cooling, the reaction solution was transferred to a 1000 D dialysis bag, and deionized water was used as the dialysis solution. The dialysis solution was changed every 12 h, and dialyzed for 48 h to remove unreacted substances. The solution was then dried at 40 °C to obtain high-purity B-GQDs powder.
[0064] 2) Single-layer or few-layer Ti3C2T x Preparation: 1.0 g Ti3AlC2 powder was slowly added to an etching solution consisting of 20 mL hydrochloric acid (9 mol / L) and 1.0 g lithium fluoride, and the mixture was stirred at 40 °C for 36 h. After the reaction, the supernatant was washed with deionized water until the pH of the supernatant reached 6. The precipitate was dispersed in 100 mL of deionized water and ultrasonically exfoliated for 2 h (200 W) under nitrogen protection. Then, it was centrifuged at 3500 rpm for 30 min, and the supernatant dispersion was collected and dried under vacuum at 40 °C to obtain monolayer or few-layer Ti3C2T. x Nanoparticle powder.
[0065] 3) B-GQDs / Ti3C2T x Preparation of composite material: Take the above B-GQDs powder and Ti3C2T x The powders were mixed (mass ratio 3:6) and dissolved in methanol to form a suspension with a mass concentration of 0.2 mg / mL. The suspension was ultrasonicated in a water bath for 60 min and then magnetically stirred at room temperature for 12 h to obtain B-GQDs / Ti3C2T. x Composite material dispersion. Transmission electron microscope image (e.g.) Figure 1 The results show that B-GQD nanoparticles are uniformly attached to Ti3C2T x No obvious aggregation phenomenon was observed on the surface of the nanosheets.
[0066] Example 2 This embodiment provides a B-GQDs / Ti3C2T x The composite-modified electrochemical electrode is prepared by the following method: 1) Place the commercial screen-printed electrode (working electrode is carbon electrode, reference electrode is silver / silver chloride electrode, counter electrode is carbon electrode) in anhydrous ethanol and ultrasonically clean for 5 min. After cleaning, rinse with deionized water and dry with nitrogen gas for later use.
[0067] 2) Using the B-GQDs / Ti3C2T prepared in Example 1 x The composite material dispersion is a modifying raw material, and it should be ultrasonically dispersed for 30 minutes before use to ensure uniformity.
[0068] 3) Take 5 μL of the above B-GQDs / Ti3C2T x The composite material dispersion was drop-coated onto the working electrode area of a screen-printed electrode. After drying at room temperature for 10 min to allow complete solvent evaporation, 5 μL of the dispersion was drop-coated again and dried in the same manner. This drop-coating-drying process was repeated twice, and the working electrode area was rinsed with deionized water to remove any unadhered composite material, yielding B-GQDs / Ti3C2T. x Electrochemical electrodes modified with composite materials.
[0069] 4) The modified electrode was allowed to age at room temperature for 12 hours to stabilize the modified layer. The resulting electrode was then stored in a dry, light-protected environment for later use. A scanning electron microscope image of the working area of the electrode is shown below. Figure 2 As shown.
[0070] Example 3 This embodiment provides B-GQDs / Ti3C2T x Plotting the standard curve of ammonia using a composite modified electrode: Ammonium chloride standard solutions of different concentrations (10, 20, 30, 40, 50, 60 μmol / L) were prepared, using 0.1 mol / L phosphate buffer solution as the supporting electrolyte. The B-GQDs / Ti3C2T prepared in Example 2 were then used... x The modified electrode was immersed in ammonium chloride standard solutions of different concentrations, and differential pulse voltammetry was used for testing (scanning potential range: -1.5~0.5 V, pulse amplitude: 50 mV, pulse width: 50 ms). The oxidation peak current values at each concentration were recorded, and a standard curve was plotted with ammonia concentration on the x-axis and peak current values on the y-axis (e.g., ...). Figure 3 (As shown).
[0071] Within the ammonia concentration range of 10–60 μmol / L, the peak current exhibits a good linear relationship with the concentration. Calibration curve: y = 0.03x + 1.00 (R²) 2 =0.94).
[0072] Where y represents the DPV oxidation peak current (μA), and x represents the ammonia concentration (μmol / L). The detection limit of this modified electrode is calculated to be 3.02 μmol / L (S / N=3), and the sensitivity is 3.32 μA·μmol·L. -1 .
[0073] Example 4 This embodiment provides B-GQDs / Ti3C2T x Plotting the standard curve of cadmium ions for the composite modified electrode: Cadmium chloride standard solutions of different concentrations (10, 20, 30, 40, 50, 60, 70, 80 μmol / L) were prepared, using 0.1 mol / L phosphate buffer solution as the supporting electrolyte. The B-GQDs / Ti3C2T prepared in Example 2 were then used... x The modified electrode was immersed in cadmium chloride standard solutions of different concentrations, and differential pulse voltammetry was used for testing (scanning potential range: -1.2~0.5 V, pulse amplitude: 50 mV, pulse width: 50 ms). The oxidation peak current values at each concentration were recorded, and a standard curve was plotted with cadmium ion concentration on the x-axis and peak current values on the y-axis (e.g., ...). Figure 4 (As shown).
[0074] Within the cadmium ion concentration range of 10–80 μmol / L, the peak current exhibits a good linear relationship with the concentration. Calibration curve: y = 0.04x + 1.62 (R²) 2 =0.98).
[0075] Where y represents the DPV oxidation peak current (μA), and x represents the cadmium ion concentration (μmol / L). The detection limit of this modified electrode is calculated to be 2.25 μmol / L (S / N=3), and the sensitivity is 2.475 μA·μmol·L. -1 .
[0076] Example 5 This embodiment provides the application of B-GQDs / Ti3C2T. x Detection of ammonia content in water samples using composite modified electrodes: A 10 mL water sample from an aquaculture body was filtered through a 0.22 μm filter membrane. Using a 0.1 mol / L phosphate buffer solution as the supporting electrolyte, 10 μmol / L standard ammonia solution was added to the aquaculture water. The B-GQDs / Ti3C2T prepared in Example 2 was then used. x The modified electrode was tested using differential pulse voltammetry under the same conditions as in Example 3, and the oxidation peak current was measured to be 0.92 μA. Substituting this peak current value into the standard curve obtained in Example 3, the ammonia concentration in the water sample was calculated to be 10.58 μmol / L, with a recovery rate of 1.06%, indicating that the B-GQDs / Ti3C2T provided by this invention... x The modified electrode exhibits high accuracy in detecting ammonia in actual water samples.
[0077] Example 6 This embodiment provides the application of B-GQDs / Ti3C2T. x Detection of cadmium ion content in water samples using composite modified electrodes: A 10 mL water sample from an aquaculture body was filtered through a 0.22 μm filter membrane. Using a 0.1 mol / L phosphate buffer solution as the supporting electrolyte, a 10 μmol / L cadmium ion standard was added to the aquaculture water. The B-GQDs / Ti3C2T standard prepared in Example 2 was then used. x The modified electrode was tested using differential pulse voltammetry under the same conditions as in Example 4, and the oxidation peak current was measured to be 2.13 μA. Substituting this peak current value into the standard curve obtained in Example 4, the cadmium ion concentration in the water sample was calculated to be 10.25 μmol / L, with a recovery rate of 1.03%, indicating that the B-GQDs / Ti3C2T provided by this invention... x The modified electrode exhibits high accuracy in detecting cadmium ions in actual water samples.
[0078] Example 7 The B-GQDs / Ti3C2T prepared in Example 2 xThe composite-modified electrode was immersed in a 20 μmol / L ammonium chloride standard solution, and its oxidation peak current was detected using differential pulse voltammetry. The electrode was then removed, rinsed with deionized water, and immersed in a 0.1 mol / L phosphate buffer solution blank support electrolyte. Cyclic voltammetry was used to scan three times within the potential range of -1.5 to 0.5 V to remove adsorbed ammonia molecules from the electrode surface and restore electrode activity. The above steps were repeated five times, and the results are as follows: Figure 5 As shown. The results indicate that the B-GQDs / Ti3C2T prepared in this invention... x The composite modified electrode exhibits excellent reusability; after five cycles, the oxidation peak current still retains more than 95% of its initial value.
[0079] Example 8 The B-GQDs / Ti3C2T prepared in Example 2 x The composite-modified electrode was immersed in a 20 μmol / L cadmium chloride standard solution, and its oxidation peak current was detected using differential pulse voltammetry. The electrode was then removed, rinsed with deionized water, and immersed in a 0.1 mol / L phosphate buffer solution blank support electrolyte. Cyclic voltammetry was used to scan three times within the potential range of -1.2 to 0.5 V to remove adsorbed ammonia molecules from the electrode surface and restore electrode activity. The above steps were repeated five times, and the results are as follows: Figure 6 As shown. The results indicate that the B-GQDs / Ti3C2T prepared in this invention... x The composite modified electrode exhibits excellent reusability; after five cycles, the oxidation peak current still retains more than 95% of its initial value.
[0080] Example 9 This embodiment provides B-GQDs / Ti3C2T x Batch-to-batch repeatability testing of composite modified electrodes: Following the preparation method in Example 2, five B-GQDs / Ti3C2T were prepared in different batches. x Composite modified electrode. Five electrodes were immersed in a 10 μmol / L mixed solution of ammonium chloride and cadmium chloride, respectively. Differential pulse voltammetry was used for detection under the same testing conditions as in Example 3, and the oxidation peak current values of each electrode were recorded. The results are as follows: Figure 7 As shown, the relative standard deviation (RSD) of the oxidation peak current of the five electrodes is 6.61%. The results indicate that the B-GQDs / Ti3C2T prepared in this invention... x The composite modified electrode exhibits good batch-to-batch repeatability, and the preparation process is stable and reliable.
[0081] Example 10 This embodiment provides B-GQDs / Ti3C2T x Anti-interference test of composite modified electrode: Different interfering substances were added to a 10 μmol / L mixed solution of ammonium chloride and cadmium chloride. These interfering substances included: Na... + (100 μmol / L), K + (100 μmol / L), Ca 2+ (100 μmol / L), Cl - (100 μmol / L), NO3 - (100 μmol / L), SO4 2- (100 μmol / L). The B-GQDs / Ti3C2T prepared in Example 2... x The composite modified electrodes were immersed in the above mixed solutions, and the oxidation peak current values were detected under the same test conditions as in Example 3. These values were then compared with the peak current values measured by the electrodes in a mixed solution containing only 10 μmol / L ammonium chloride and cadmium chloride. Figure 8 As shown in the figure. The results indicate that the presence of the aforementioned interfering substances has an impact of less than ±9% on the detection signals of ammonia and cadmium ions, demonstrating that the B-GQDs / Ti3C2T prepared in this invention... x Composite modified electrodes exhibit good anti-interference performance.
[0082] Example 11 This embodiment provides B-GQDs / Ti3C2T x Optimal response time test of modified electrode: The B-GQDs / Ti3C2T prepared in Example 2 x The composite-modified electrode was immersed in a 10 μmol / L mixed solution of ammonium chloride and cadmium chloride. Differential pulse voltammetry was used to continuously measure the oxidation peak current at different time points (1, 2, 3, 4, 5, and 6 min), and the peak current variation curve over time was recorded. Figure 9 The results showed that the oxidation peak current tended to stabilize and reach its maximum value at approximately 4 min, after which the current value remained essentially constant. Therefore, this B-GQDs / Ti3C2T x The optimal response time of the composite modified electrode is 4 min, indicating that the modified electrode has a rapid response capability to ammonia and cadmium ions in water.
[0083] Example 12 This embodiment uses the same method as in Example 2 to prepare the modified electrode, the only difference being the different mass ratios of B-GQDs and Ti3C2T. x Preparation of composite material dispersion. B-GQDs and Ti3C2T x The resistance of modified electrodes with different mass ratios is as follows Figure 10 As shown. The unmodified bare electrode exhibits the highest impedance after being processed by B-GQDs and Ti3C2T.x The mass ratios are 0:3 (pure Ti3C2T) x The electrode impedance decreased with 3:0 (pure B-GQDs) and 3:0 (pure B-GQDs) modifications, indicating that B-GQDs are compatible with Ti3C2T. x B-GQDs exhibit good electrical conductivity, but their tendency to aggregate limits electron transfer. When B-GQDs are combined with Ti3C2T... x Increased mass ratio, Ti3C2T x The B-GQDs were sufficiently dispersed to construct a highly efficient conductive network, while the B-GQDs provided enough recognition sites. In the interaction between B-GQDs and Ti3C2T... x When the mass ratio is 3:6, the electrode exhibits a good current signal and minimal impedance. When B-GQDs and Ti3C2T... x If the mass ratio exceeds a certain range, a thicker film will form, hindering electron transfer and ion diffusion at the electrode-electrolyte interface, resulting in a decrease in the current signal.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrochemical electrode, characterized in that, Includes a substrate and a sensitive modification material attached to the substrate; the sensitive modification material is B-GQDs and Ti3C2T. x The composite material, wherein the substrate is a screen-printed electrode.
2. The electrochemical electrode according to claim 1, characterized in that, The B-GQDs and Ti3C2T x The mass ratio is 1~10:1~30.
3. The electrochemical electrode according to claim 1 or 2, characterized in that, The preparation of the electrochemical electrode includes: preparing a mixture of the B-GQDs and Ti3C2T. x A mixed composite material dispersion; the composite material dispersion is drop-coated onto the working electrode area of a screen-printed electrode and then dried.
4. The electrochemical electrode according to claim 3, characterized in that, The preparation of the B-GQDs includes: using boron-containing precursors and carbon sources as raw materials, and preparing them through a hydrothermal reaction.
5. The electrochemical electrode according to claim 3, characterized in that, The Ti3C2T x The preparation process includes mixing Ti3AlC2 with a fluorine-containing etching solution, followed by selective etching and ultrasonic stripping.
6. A method for preparing the electrochemical electrode according to any one of claims 1-5, characterized in that, include: 1) A boron-containing precursor and a carbon source are mixed and subjected to a hydrothermal reaction to obtain B-GQDs; 2) Ti3AlC2 was mixed with a fluorine-containing etching solution, and then selectively etched and ultrasonically stripped to obtain Ti3C2T. x ; 3) The B-GQDs and Ti3C2T x The mixture is combined with a solvent, and then subjected to ultrasonication and stirring to obtain a dispersion. 4) The dispersion is drop-coated onto the working electrode area of the screen-printed electrode and then dried.
7. The method for preparing the electrochemical electrode according to claim 6, characterized in that, In step 3), the B-GQDs and Ti3C2T x The mass ratio is 1~10:1~30.
8. The electrochemical electrode according to claim 6 or 7, characterized in that, In step 3), the concentration of the dispersion is 0.02~0.5 mg / mL.
9. The application of the electrochemical electrode according to any one of claims 1-5 or the electrochemical electrode prepared by the preparation method according to any one of claims 6-8 in water quality detection.
10. The application according to claim 9, characterized in that, Application in the detection of ammonia and / or cadmium ion content in water.
Citation Information
Patent Citations
Electrochemical sensor for detecting heavy metal cadmium ions as well as construction method and application of electrochemical sensor
CN117074485A
Novel platinum-nickel alloy electrochemical sensor for detecting ammonia nitrogen as well as preparation method and application of novel platinum-nickel alloy electrochemical sensor
CN117740896A
Electrochemical detection of monochloramine and / or ammonia
CN121844201A
